Legal Protection for Practice Students D3 Medical Record and Health Information UNU NTB in NTB Province Hospital - Muhamad Siladani Fatuhu; Dwi Andayani (STIKes Patria Husada Blitar, 2022)
Hospitals have an obligation to provide safe, quality, anti-discriminatory and effective health services with hospital service standards. Kepmenkes No. 377 of 2007 concerning Professional Standards for Medical Recorders and Health Information. Medical Recorder and Health Information is someone who has passed the formal education of medical records and health information, has full competence, duties, responsibilities, authority and rights to carry out medical recording activities. Sari Ulina's 2008 research on a health worker who published the autopsy results of a murder victim so that he was sued in court. The purpose of this study was to find out the implementing regulations for practical students, to find out the forms of legal protection for practical students, and to find out the efforts of hospital institutions in providing legal protection to D3 RMIK UNU NTB students at the NTB Provincial Hospital. This study uses a sociological juridical approach, descriptive analytic with the types of data in the form of primary and secondary (primary legal materials), while the data collection technique is by means of interviews consisting of 4 sources where the sample selection uses purposive sampling. Based on the research results obtained, the form of regulations for implementing the practice of RMIK D3 students is in the form of SOPs with No. 047/08/15/2018 Dated 29-12-2018 which is a derivative of the director's decree No: 821/444/RSUD Prov. NTB Concerning the Enforcement of Clinical Practice Guidelines for Other Health Workers, while the form of legal protection for students is to carry out SOPs and/or rules that have been imposed by the hospital. Meanwhile, the hospital's efforts to provide legal protection for D3 RMIK UNU NTB students are by providing guidance and obeying the rules imposed by the hospital because students do not yet have the competence in carrying out the practice of medical recorders and health information.